PENGARUH KADAR GARAM TERHADAP DAYA YANG DIHASILKAN PEMBANGKIT LISTRIK TENAGA AIR GARAM SEBAGAI ENERGI ALTERNATIF TERBARUKAN - Arizal, Fachrul; Hasbi, Muhammad; Kadir, Abd (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The purpose of this study is to find out of salinity towards electric power produced by salt water power plants as a renewable alternative electrical energy. Tool and materials used in this research were the AVO meter, pliers, copper plate, aluminium plate, ruler, measuring cups, balance analitik, salt meter, salt, copper plate, aluminum plate, cable and glass. The procedure of this study was preparing tools and materials, then making an electrochemical cell as much as 2 pairs of electrochemical cells and a container of water and salt using glass with 2 liter volume of water, making the series circuit copper plate and aluminum, making a solution of water and salt, then testing the power of salt water as a source alternative energy using AVO meter. The parameters measured in this study was a large electric potential and strong currents are able to produce brine with amounts of salt variety 25 g, 50 g, 75 g, 100 g, 125 g, 150 g, 175 g, 200 g and 225 g, done to provide different salinity. After testing the brine into alternative energy sources, large power obtained on the salinity 74% or with mass of salt 175 g which produce the power that is equal to 0058 watts, while the value of the lowest power contained in the salinity of 7% or the mass of salt 25 g, where only capable to produce the electric power amounting of 0,011 Watt. To turn on the LED lamp 1.5 W using electrochemical cells method can be done by making the cells as much as 20 cells with a volume of 2,000 ml of water and salt mixed with 175 g of salt with a salt content of 74%. Using 20 pairs of aluminum and copper electrode cell where each electrode measuring 3 cm x 6 cm.Keywords: Brine, electrochemical cells, salinity and power.